RECTANGULAR CUFFS OVERESTIMATE BLOOD PRESSURE IN OBESE PEOPLE WITH VERY LARGE ARMS. (June 2018) - Palatini, P.; Benetti, E.; Fania, C.; Saladini, F.
Abstract : Objective: Rectangular cuffs and bladders are currently used for blood pressure (BP) measurement at the upper arm. However, large arms always have a tronco-conical shape. Aim of this study was to ascertain whether rectangular and tronco-conical cuffs provide different readings in obese subjects with very large arms. Design and method: In 33 subjects with morbid obesity (BMI, 45 ± 5.0 Kg/m2.16 men) aged 51 ± 12 years, with arm mid-circumference ranging from 42 to 55 cm, and 33 subjects of control with standard arm circumference (range, 22–31 cm) the upper-arm frustum slant angle was measured. Two different rectangular and two different tronco-conical bladders of appropriate size and shape were constructed, on the basis of previous anthropometric measures obtained in our laboratory. In each subject, BP was measured in triplicate by two observers using the two cuffs in a random order. In addition, in the obese participants, the pressure under the two cuffs was measured at five pressure levels (60, 90, 120, 150 and 180 mmHg) using a paper-thin pressure sensor attached to the central point of the cuffs. Results: In all obese participants the upper arm shape was tronco-conical with slant angles ranging from 80.4 to 87.6° (mean 84.1 ± 1.4°). Systolic BP (SBP) and diastolic BP (DBP) differences between the troncoconical and the rectangular cuff were −4.8 ± 4.0 and −3.0 ± 4.3 mmHg, respectively, whereas they were negligible in the controls (SBP, p < 0.001 and DBP, p = 0.01). In the subjects of the top SBP quintile (SBP > = 150 mmHg), the between-cuff SBP difference was −9.1 ± 5.1 mmHg. Arm slant angle was an independent predictor of the between-cuff SBP discrepancy (p = 0.003). Measurement with the pressure sensor showed a higher pressure under the rectangular compared to the conical cuff at any pressure level. The mean difference was −10.2 ± 5.2 mmHg and the difference progressively increased with increasing level of pressure applied to the cuffs. Conclusions: In obese people, the upper arm has a pronounced tronco-conical shape and rectangular cuffs may overestimate BP. Tronco-conical cuffs should be used for BP measurement in subjects with very large arms.